2019
DOI: 10.3390/ijms20081833
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Standardized Cannabis sativa L. Extract and Its Constituent Cannabidiol Inhibit Human Polymorphonuclear Leukocyte Functions

Abstract: Cannabis and cannabinoids offer significant therapeutic benefits for a wide scope of pathological conditions. Among them, the clinical issues rooted in inflammation stand out, nonetheless, the underlying mechanisms are not yet plainly understood. Circumstantial evidence points to polymorphonuclear leukocytes (PMN) as targets for the anti-inflammatory effects of cannabis. Therefore, we conducted this study to assess the effects of CM5, a novel Cannabis sativa L. extract standardized in 5% cannabidiol (CBD), on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 48 publications
3
26
0
1
Order By: Relevance
“…Similarly, activation of the GPR55 receptor present on neutrophils leads to a reduction in the production of ROS, as well as degranulation [ 58 ]. On the other hand, in previous studies CBD has not shown an effect on neutrophil viability [ 18 ] and its effect on NETosis has not been analyzed. In the study presented here, our results show that CBD decreases rate of NETosis in neutrophils and also production of most of markers of NETosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, activation of the GPR55 receptor present on neutrophils leads to a reduction in the production of ROS, as well as degranulation [ 58 ]. On the other hand, in previous studies CBD has not shown an effect on neutrophil viability [ 18 ] and its effect on NETosis has not been analyzed. In the study presented here, our results show that CBD decreases rate of NETosis in neutrophils and also production of most of markers of NETosis.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of CBD on neutrophils have not been sufficiently studied so far. CBD has recently been observed to inhibit neutrophil migration and their production of ROS, since preincubation of neutrophils with CBD leads to significantly lower ROS levels [ 18 ]. As mentioned above, cannabidiol works by activating specific receptors, in the case of immune cells mainly through CB2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Our DDG search on the Internet found more indications for CBD, including in the treatment of oral and genital herpes, HIV/AIDS, cold and flu, shingles, hepatitis C, Ebola, mononucleosis, progressive multifocal leukoencephalopathy, and West Nile and Zika fevers. Reportedly, the antiviral potential of CBD lies in the fact that it may affect both the innate and adaptive immune cells functions 29,30 and host inflammatory responses play a critical role in the pathogenesis of these viral diseases. However, apart from hepatitis C, there is a very real lack of scientific evidence supporting the other alleged antiviral properties of CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the anti-inflammatory effects of cannabis are likely through the suppression of PMN function. PMNs express the cannabinoid receptor (CB2) (176) and evidence suggests that cannabinoids suppress PMN function including cell migration, production of ROS and TNF-α production (177). In vivo, inhibition of the CB2 receptor suppressed PMN-mediated tissue damage in a mouse model of myocardial ischemia/reperfusion injury (178), and mice that lack CB2 expression exhibit exacerbated PMN recruitment during infection (179).…”
Section: Potential Therapeutic Pmn-specific Interventionsmentioning
confidence: 99%